A comprehensive approach to conservation of ancient graffiti at El Kurru, Sudan. Issue 1 (3rd April 2018) - Davis, Suzanne L.; Roberts, Caroline; Batkin-Hall, Janelle
ABSTRACT: This paper describes conservation and preservation of ancient Meroitic graffiti in a rock-cut temple at the site of El Kurru in Sudan. The temple and its graffiti provide important material evidence for the African empire of Kush, but El Kurru's sandstone monuments suffer from granular disintegration and other serious condition problems. Although the conservation of archaeological heritage is often complicated, it is especially challenging in Sudan due to a fragile national economy and, until October 2017, United States sanctions against the country. A comprehensive, investigation-based approach has been used in conservation planning for the graffiti. Work began with a criterion-anchored rating condition survey designed to identify, prioritize, and monitor condition issues. Chemical analysis of the stone was conducted, and treatment options including alkoxysilane consolidation and grout injection were explored. Preventive conservation strategies for the temple, including a protective shelter and increased community education, have also been examined. Finally, reflectance transformation imaging was used to document the graffiti's condition and create a virtual, visual catalog. In description of these activities, the paper emphasizes key principles for guiding conservation at archaeological sites: practicality, flexibility, sustainability, and placing a high value on the contributions and wishes of stakeholders.